MALAYSIA – INDONESIA: IN THE VORTEX OF INTERPRETATION - Sulistiyono, Bambang B; Hjaazi, Mohd Zaidi (JURNAL ILMIAH M-PROGRESS, 2019)
Malaysia and Indonesia are two countries with a relationship that is very unique. Its society has established kinship long before the two countries was formed, which resulted similarities in each other’s culture and customs. Both countries also play a very important role in associations of the Southeast Asian nations that is accommodated through the ASEAN forum.   However, the relationship between Malaysia and Indonesia have not always been great, sometimes it touches the lowest state and at other times at the most harmonious. The Realist and Liberalist theory applies in studying relations between these two countries. Although waves of problems coming and going may occur naturally, plenty of formal efforts has also been done by both governments.   There are three interesting time periods in this study; the relationship period most bitter (1963-1966), the most harmonious relationship period (1968-1982), and the period of friendly but tense relations (1983-2010). Assessment of the two countries’ relationship dynamics is done through in qualitative approach with comparative analaysis and  supported by the "Taxonomy Bloom" method.   Many main informans with different backgrounds are the core informants who supported this study. Some are former government officials, academicians, military personnel and citizens who have had a history of being directly involved in the confrontation and many of the accuracy of data information can produce .  From a comprehensive study a case was found, identifying that interpretation differences as well as similarities is what causes the two countries’ relationship experience highs and lows. Also through this study, the root of the problem can be understood therefore suggestion of solutions can be submitted. Key words : Interpretation, Conflict And Cooperation